Method for preparing graphene by plasma-assisted ball milling

Through the plasma-assisted ball milling method, the nitrogen-water vapor mixed gas treatment and special ball milling media and release agents are used to solve the problems of high energy consumption and environmental pollution in the existing graphene preparation process, and high-quality and large-scale graphene preparation is achieved, which improves the single-layer rate and conductivity.

CN120534963AActive Publication Date: 2025-08-26DINGYUAN DONGCHANG CARBON-BASED MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510999609.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2025-08-26
Estimated Expiration
2045-07-21

AI Technical Summary

Technical Problem

The existing graphene preparation process has problems such as harsh conditions, high energy consumption, serious environmental pollution and low product output, making it difficult to achieve high-quality and large-scale graphene preparation.

Method used

The plasma-assisted ball milling method is used to treat graphite raw materials through a nitrogen-water vapor mixture gas, combined with a special ball milling medium and release agent, including zirconia ceramic core and modified cellulose nanocrystals, to coordinate the graphite layer to form high-purity and high-quality graphene.

Benefits of technology

The single-layer rate and conductivity of graphene are improved, the wear rate of ball milling media is reduced, the peeling efficiency is enhanced, and the recycling of resources is realized, and high-purity and high-quality graphene products are obtained.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of graphene preparation, and particularly relates to a method for preparing graphene through plasma-assisted ball milling. According to the method, the nitrogen-water vapor mixed gas is adopted, through pulse plasma dual-mode treatment, the expansion distance is formed between graphite layers, the interlayer distance is increased, the nanometer pits are formed in the graphite surface in an etching mode, the roughness and active sites of the graphite surface are increased, sufficient contact between a subsequent ball milling medium and the graphite is facilitated, and then the ball milling efficiency is improved. A used ball milling medium is prepared from electronic waste and rice husks, so that cyclic utilization of resources is achieved, meanwhile, good wear resistance and chemical stability are achieved, proper friction force and shearing force are provided in the ball milling process, and efficient stripping is achieved in cooperation with weakening interlayer force after plasma treatment. The stripping agent promotes the preparation of a high-purity and high-quality graphene product through the mutual cooperation of the modified cellulose nanocrystal, the citrate surfactant and the glucose-derived carbon quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene preparation, and particularly relates to a method for preparing graphene by utilizing plasma-assisted ball milling. Background Art

[0002] Graphene's unique physical and chemical properties, due to its single-atom-thick, two-dimensional structure, hold enormous potential for applications in a wide range of fields, including energy storage, transparent electrodes, lithium-ion batteries, solar cells, fuel cells, and building materials. Therefore, research into high-quality, large-scale graphene production processes is crucial. Numerous methods for graphene production have been developed, including the initial micromechanical exfoliation method, epitaxial growth, chemical vapor deposition (CVD), electrochemical methods, and redox methods.

[0003] While previous research has improved graphene preparation processes to some extent, these processes often involve harsh conditions, high energy consumption, and severe environmental pollution. Furthermore, most processes are not continuous, resulting in low and unstable product yields. Therefore, exploring more suitable new graphene preparation processes is crucial for achieving industrial applications. Summary of the Invention

[0004] The purpose of the present invention is to address the existing problems and provide a method for preparing graphene by plasma-assisted ball milling.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing graphene by plasma-assisted ball milling comprises the following steps:

[0007] S1, crushing the flake graphite and placing it in a plasma reaction chamber, introducing a nitrogen-water vapor mixed gas, and performing plasma treatment;

[0008] S2, adding the plasma-treated graphite raw material, ball milling medium, and stripping agent into a ball milling tank for ball milling;

[0009] S3. Centrifugal treatment is performed to remove the ball milling medium, dialysis treatment is performed to remove the stripping agent, and then freeze-drying treatment is performed.

[0010] Furthermore, the volume ratio of nitrogen to water vapor in the nitrogen-water vapor mixed gas described in step S1 is 8:2, and the plasma treatment is specifically as follows: first turn on the pulse plasma power supply, adjust the power frequency to 10 kHz, the voltage to 100 V, and treat for 10 to 12 minutes, then adjust the power frequency to 50 kHz, the voltage to 300 V, and treat for 5 to 6 minutes.

[0011] Furthermore, the ball-to-material ratio during the ball milling process in step S2 is 15-25:1.

[0012] Furthermore, the preparation of the ball milling medium described in step S2 includes the following steps:

[0013] (1) The collected waste electronic components of zirconia ceramic parts were crushed to a particle size of less than 5 mm, and then added to a mixture of 10% hydrochloric acid solution and 20% sodium hydroxide solution in a volume ratio of 1:1. After stirring at room temperature for 3-4 hours, the mixture was rinsed with deionized water until neutral and dried to obtain zirconia particles.

[0014] (2) Adding 3% by mass of a Y2O3 stabilizer and 5% by mass of a sodium carboxymethyl cellulose aqueous solution to the above-mentioned zirconium oxide particles, stirring and mixing, and then cold isostatically pressing to obtain a green body, placing the green body in a high-temperature sintering furnace, heating it to 1600°C at a rate of 8-10°C / min, and keeping it at that temperature for 3-4 hours to obtain a zirconium oxide ceramic core;

[0015] (3) The slurry is sprayed onto the surface of the zirconia ceramic core using a spraying method, with a thickness of 15-25 μm, and then sintered in an argon atmosphere at 1300 °C for 1-2 hours.

[0016] Furthermore, the preparation of the slurry described in step (3) comprises the following steps:

[0017] A. After the dried rice husk is crushed to a particle size of less than 1 mm, it is placed in a muffle furnace and carbonized at 700°C for 5-6 hours to obtain carbon powder. The carbon powder, sodium carbonate, and magnesium powder are fully mixed in a mass ratio of 1:3:2, and then placed in a vacuum tube furnace. Under argon protection, the temperature is raised from 6-7°C to 850°C. The temperature is kept at this temperature for 3-4 hours and then cooled. The product is placed in a mixture of hydrochloric acid (15%) and HF acid (hydrofluoric acid, 0.3%) in a volume ratio of 10:1 and soaked for 10-12 hours. The product is washed with water until neutral and then dried to obtain bio-silicon carbide powder;

[0018] B. Mix bio-based silicon carbide powder and water in a mass ratio of 1:5, then add 3% by mass of sodium alginate and stir until well mixed.

[0019] Furthermore, the preparation of the stripping agent described in step S2 includes the following steps:

[0020] 1) Microcrystalline cellulose was ground and passed through a 100-mesh sieve. The mixture was then mixed with a 60% by mass sulfuric acid solution at a solid-to-liquid ratio of 1:10 and stirred in a constant temperature water bath at 40-50°C for 80-100 minutes. The sulfuric acid solution was then diluted with deionized water until it was nearly neutral, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until the conductivity of the washing solution was less than 10 μS / cm to obtain cellulose nanocrystals.

[0021] 2) Cellulose nanocrystals were ultrasonically dispersed in an ethanol-water solution (ethanol:water = 1:1, v / v). After uniform dispersion, 3-aminopropyltriethoxysilane (APTES) (0.1 times the mass of the cellulose nanocrystals) was added and stirred at 40-50°C for 3-4 hours. Unreacted APTES was then removed by dialysis (dialysis bag molecular weight cutoff 3500Da). The modified cellulose nanocrystals were then acetylated with acetic anhydride to control the degree of substitution to 0.2.

[0022] 3) Add the modified cellulose nanocrystals, citrate surfactant, and glucose-derived carbon quantum dots into deionized water at a mass ratio of 16:3:1, and stir at 8000-10000 rpm for 30-40 minutes at room temperature.

[0023] Furthermore, the preparation method of the citrate surfactant described in step 3) is as follows: citric acid and polyethylene glycol 400 are added to a reactor in a molar ratio of 1:3, and then 1% by weight of citric acid and p-toluenesulfonic acid are added as a catalyst, and the esterification reaction is carried out at 120-130°C for 6-7 hours. After the reaction is completed, a saturated sodium carbonate solution is added to neutralize the catalyst, and the pH is adjusted to 7-8. The organic phase is then separated using a separatory funnel, washed with deionized water 3-4 times, and then distilled under reduced pressure.

[0024] Furthermore, the preparation method of the glucose-derived carbon quantum dots described in step 3) is as follows: glucose and deionized water are mixed in a mass ratio of 1:10, 0.1M citric acid is added, and a hydrothermal reaction is carried out at 180~190°C for 3~4h. After the reaction is completed, it is filtered through a 0.22μm filter membrane, and then dialyzed (the dialysis bag has a molecular weight cutoff of 1000Da) to obtain a purified carbon quantum dot solution. Polyethyleneimine accounting for 5% of the mass of the carbon quantum dots is added to the purified carbon quantum dot solution. After stirring the reaction at room temperature for 2~3h, it is dialyzed again (the dialysis bag has a molecular weight cutoff of 3500Da) to obtain glucose-derived carbon quantum dots.

[0025] Furthermore, during the ball milling treatment in step S2, the ball milling speed is controlled to be 400-600 rpm, and the ball milling time is 3-5 hours.

[0026] Furthermore, the rotation speed during the centrifugation treatment in step S3 is 8000-10000 rpm, the centrifugation time is 10-15 min, the molecular weight cutoff of the dialysis bag during the dialysis treatment is 3500-5000 Da, and the dialysis time is 20-30 h.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. The present invention uses a nitrogen-water vapor mixed gas and a pulsed plasma dual-mode treatment, first at 10kHz and 100V. Nitrogen excitation generates high-energy nitrogen radicals, which react with carbon atoms between graphite layers to form nitrogen-containing functional groups. The insertion of these functional groups weakens the van der Waals forces between graphite layers. At the same time, the OH radicals generated by the dissociation of water vapor undergo an oxidation reaction with impurities on the graphite surface, converting the impurities into volatile or soluble substances, thereby cleaning the graphite surface. The frequency and voltage are then adjusted. Higher frequencies and voltages generate stronger energy, forming an expansion gap between graphite layers, increasing the interlayer distance, and etching nano-pits on the graphite surface, increasing the roughness and active sites of the graphite surface, which helps to fully contact the subsequent ball milling medium with the graphite, thereby enhancing the ball milling efficiency.

[0029] 2. The ball milling media of the present invention is prepared using electronic waste and rice husks as raw materials, realizing resource recycling. Y2O3 stabilizer is added and the sintering process is optimized in the preparation of the zirconia ceramic core to improve the structural stability and wear resistance of the core. Rice husk is used as raw material and a unique preparation process is adopted to ensure that the coating layer is tightly combined with the core, while having good wear resistance and chemical stability. It provides appropriate friction and shear force during the ball milling process, and cooperates with the interlayer force weakened after plasma treatment to achieve efficient peeling.

[0030] 3. During the preparation of the stripping agent of the present invention, functional groups such as amino and acetyl groups are introduced through acid hydrolysis, APTES modification, and acetic anhydride acetylation treatment, thereby improving the dispersibility of cellulose nanocrystals. The modified cellulose nanocrystals are adsorbed on the surface of graphene to form a hydration layer, generating a steric hindrance effect, hindering the agglomeration of graphene sheets. The citrate surfactant reduces the interfacial energy between graphite and the medium and the stripping agent, making the graphene easier to strip during the ball milling process. The carbon quantum dots are embedded between the graphite layers, expanding the interlayer spacing, and synergistically promoting the exfoliation and dispersion of the graphene, thereby helping to obtain high-purity, high-quality graphene products. DETAILED DESCRIPTION

[0031] In order to further explain the present invention, it is described below with reference to the following specific embodiments.

[0032] Example 1

[0033] A method for preparing graphene by plasma-assisted ball milling comprises the following steps:

[0034] S1. Crushed flake graphite was placed in a plasma reaction chamber and introduced with a nitrogen-water vapor mixture (nitrogen to water vapor volume ratio of 8:2). The pulse plasma power supply was first turned on, and the power supply frequency was adjusted to 10 kHz and the voltage to 100 V for 10 minutes. Then the power supply frequency was adjusted to 50 kHz and the voltage to 300 V for 5 minutes.

[0035] S2. Add the plasma-treated graphite raw material, ball milling medium, and stripping agent into a ball mill with a ball-to-material ratio of 15:1 and mill at 400 rpm for 3 h.

[0036] The preparation of the ball milling medium comprises the following steps:

[0037] (1) The collected waste electronic components of zirconia ceramic parts were crushed to a particle size of less than 5 mm, and then added to a mixture of 10% hydrochloric acid solution and 20% sodium hydroxide solution in a volume ratio of 1:1. After stirring at room temperature for 3-4 hours, the mixture was rinsed with deionized water until neutral and dried to obtain zirconia particles.

[0038] (2) Adding 3% by mass of a Y2O3 stabilizer and 5% by mass of a sodium carboxymethyl cellulose aqueous solution to the above-mentioned zirconium oxide particles, stirring and mixing, and then cold isostatically pressing to obtain a green body, placing the green body in a high-temperature sintering furnace, heating it to 1600°C at a rate of 8°C / min, and keeping it at that temperature for 3 hours to obtain a zirconium oxide ceramic core;

[0039] (3) After the dried rice husk is crushed to a particle size of less than 1 mm, it is placed in a muffle furnace and carbonized at 700 °C for 5 h to obtain carbon powder. The carbon powder, sodium carbonate, and magnesium powder are fully mixed in a mass ratio of 1:3:2, and then placed in a vacuum tube furnace. Under argon protection, the temperature is raised from 6 °C to 850 °C, kept warm for 3 h, and then cooled. The product is placed in a mixture of hydrochloric acid (15%) and HF acid (0.3%) with a volume ratio of 10:1 and soaked for 10 h. The product is washed with water until neutral and then dried to obtain bio-silicon carbide powder;

[0040] (4) Bio-based silicon carbide powder and water were mixed in a mass ratio of 1:5, and then 3% of sodium alginate was added and stirred to obtain a slurry. The slurry was sprayed onto the surface of the zirconia ceramic core by spraying method with a thickness of 15 μm, and then sintered at 1300 ° C in an argon atmosphere for 1 h.

[0041] The preparation of the stripping agent comprises the following steps:

[0042] 1) Microcrystalline cellulose was ground and passed through a 100-mesh sieve. The mixture was then mixed with a 60% by mass sulfuric acid solution at a solid-to-liquid ratio of 1:10 and stirred in a constant temperature water bath at 40°C for 80 minutes. The sulfuric acid solution was then diluted with deionized water until it was nearly neutral, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until the conductivity of the washing solution was less than 10 μS / cm to obtain cellulose nanocrystals.

[0043] 2) Cellulose nanocrystals were ultrasonically dispersed in an ethanol-water solution (ethanol:water = 1:1, v / v). After uniform dispersion, 0.1 times the mass of the cellulose nanocrystals was added with APTES. The mixture was stirred at 40°C for 3 h. Unreacted APTES was then removed by dialysis (dialysis bag molecular weight cutoff 3500 Da). The modified cellulose nanocrystals were then acetylated with acetic anhydride to control the degree of substitution to 0.2.

[0044] 3) Citric acid and polyethylene glycol 400 were added to a reactor in a molar ratio of 1:3, and then p-toluenesulfonic acid (1% by weight of the citric acid) was added as a catalyst. The esterification reaction was carried out at 120°C for 6 hours. After the reaction, a saturated sodium carbonate solution was added to neutralize the catalyst, and the pH was adjusted to 7. The organic phase was separated using a separatory funnel, washed with deionized water 3-4 times, and then distilled under reduced pressure to obtain a citrate surfactant.

[0045] 4) Glucose and deionized water were mixed in a mass ratio of 1:10, 0.1 M citric acid was added, and a hydrothermal reaction was carried out at 180°C for 3 hours. After the reaction, the mixture was filtered through a 0.22 μm filter membrane and then dialyzed (with a molecular weight cutoff of 1000 Da) to obtain a purified carbon quantum dot solution. Polyethyleneimine accounting for 5% of the mass of the carbon quantum dots was added to the purified carbon quantum dot solution. After stirring at room temperature for 2 hours, the mixture was dialyzed again (with a molecular weight cutoff of 3500 Da) to obtain glucose-derived carbon quantum dots.

[0046] 5) Add modified cellulose nanocrystals, citrate surfactant, and glucose-derived carbon quantum dots to deionized water at a mass ratio of 16:3:1, and stir at 8000 rpm for 30 minutes at room temperature;

[0047] S3. Centrifuge at 8000 rpm for 10 min to remove the ball milling medium, dialyze (dialysis bag with a molecular weight cutoff of 3500 Da) for 20 h to remove the stripping agent, and then freeze-dry.

[0048] Example 2

[0049] A method for preparing graphene by plasma-assisted ball milling comprises the following steps:

[0050] S1. Crushed flake graphite was placed in a plasma reaction chamber and introduced with a nitrogen-water vapor mixture (nitrogen to water vapor volume ratio of 8:2). The pulse plasma power supply was first turned on, and the power supply frequency was adjusted to 10 kHz and the voltage to 100 V for 11 minutes. Then the power supply frequency was adjusted to 50 kHz and the voltage to 300 V for 5 minutes.

[0051] S2, adding the plasma-treated graphite raw material, ball milling medium, and stripping agent into a ball milling jar with a ball-to-material ratio of 20:1, 500 rpm, and ball milling for 4 hours;

[0052] The preparation of the ball milling medium comprises the following steps:

[0053] (1) The collected waste electronic components of zirconia ceramic parts were crushed to a particle size of less than 5 mm, and then added to a mixture of 10% hydrochloric acid solution and 20% sodium hydroxide solution in a volume ratio of 1:1. After stirring at room temperature for 3.5 hours, the mixture was rinsed with deionized water until neutral, and dried to obtain zirconia particles;

[0054] (2) Adding 3% by mass of a Y2O3 stabilizer and 5% by mass of a sodium carboxymethyl cellulose aqueous solution to the above-mentioned zirconium oxide particles, stirring and mixing, and then cold isostatically pressing to obtain a green body, placing the green body in a high-temperature sintering furnace, heating it to 1600°C at a rate of 9°C / min, and keeping it at that temperature for 3.5 hours to obtain a zirconium oxide ceramic core;

[0055] (3) The dried rice husk was crushed to a particle size of <1 mm, placed in a muffle furnace, and carbonized at 700 °C for 5.5 h to obtain carbon powder. The carbon powder, sodium carbonate, and magnesium powder were fully mixed in a mass ratio of 1:3:2, and then placed in a vacuum tube furnace. Under argon protection, the temperature was raised from 6.5 °C to 850 °C, kept warm for 3.5 h, and then cooled. The product was placed in a mixture of hydrochloric acid (15%) and HF acid (0.3%) with a volume ratio of 10:1 and soaked for 11 h. The product was washed with water until neutral and then dried to obtain bio-silicon carbide powder.

[0056] (4) Bio-based silicon carbide powder and water were mixed in a mass ratio of 1:5, and then 3% of sodium alginate was added and stirred to obtain a slurry. The slurry was sprayed onto the surface of the zirconia ceramic core by spraying method with a thickness of 20 μm, and then sintered at 1300 ° C in an argon atmosphere for 1.5 h.

[0057] The preparation of the stripping agent comprises the following steps:

[0058] 1) Microcrystalline cellulose was ground and passed through a 100-mesh sieve. The mixture was then mixed with a 60% by mass sulfuric acid solution at a solid-to-liquid ratio of 1:10 and stirred in a constant temperature water bath at 45°C for 90 minutes. The sulfuric acid solution was then diluted with deionized water until it was nearly neutral, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until the conductivity of the washing solution was less than 10 μS / cm to obtain cellulose nanocrystals.

[0059] 2) Cellulose nanocrystals were ultrasonically dispersed in an ethanol-water solution (ethanol:water = 1:1, v / v). After uniform dispersion, 0.1 times the mass of APTES by weight of the cellulose nanocrystals was added and stirred at 45°C for 3.5 hours. Unreacted APTES was then removed by dialysis (dialysis bag with a molecular weight cutoff of 3500Da). The cellulose nanocrystals were then acetylated with acetic anhydride to control the degree of substitution to 0.2, yielding modified cellulose nanocrystals.

[0060] 3) Citric acid and polyethylene glycol 400 were added to a reactor in a molar ratio of 1:3, and then p-toluenesulfonic acid (1% by weight of the citric acid) was added as a catalyst. The esterification reaction was carried out at 125°C for 6.5 hours. After the reaction, a saturated sodium carbonate solution was added to neutralize the catalyst, and the pH was adjusted to 7.5. The organic phase was then separated using a separatory funnel, washed three times with deionized water, and then distilled under reduced pressure to obtain a citrate surfactant.

[0061] 4) Glucose and deionized water were mixed in a mass ratio of 1:10, 0.1 M citric acid was added, and a hydrothermal reaction was carried out at 185°C for 3.5 hours. After the reaction, the mixture was filtered through a 0.22 μm filter membrane and then dialyzed (with a molecular weight cutoff of 1000 Da) to obtain a purified carbon quantum dot solution. Polyethyleneimine accounting for 5% of the mass of the carbon quantum dots was added to the purified carbon quantum dot solution, and the mixture was stirred at room temperature for 2.5 hours, and then dialyzed again (with a molecular weight cutoff of 3500 Da) to obtain glucose-derived carbon quantum dots.

[0062] 5) Add modified cellulose nanocrystals, citrate surfactant, and glucose-derived carbon quantum dots to deionized water in a mass ratio of 16:3:1 and stir at 9000 rpm for 35 minutes at room temperature;

[0063] S3. Centrifuge at 9000 rpm for 12 minutes to remove the ball milling medium, dialyze (dialysis bag with a molecular weight cutoff of 4000 Da) for 25 hours to remove the stripping agent, and then freeze-dry.

[0064] Example 3

[0065] A method for preparing graphene by plasma-assisted ball milling comprises the following steps:

[0066] S1. Crushed flake graphite was placed in a plasma reaction chamber and introduced with a nitrogen-water vapor mixture (nitrogen to water vapor volume ratio of 8:2). The pulse plasma power supply was first turned on, and the power supply frequency was adjusted to 10 kHz and the voltage to 100 V for 12 minutes. Then the power supply frequency was adjusted to 50 kHz and the voltage to 300 V for 6 minutes.

[0067] S2. Add the plasma-treated graphite raw material, ball milling medium, and stripping agent into a ball mill with a ball-to-material ratio of 25:1, 600 rpm, and ball mill for 5 hours;

[0068] The preparation of the ball milling medium comprises the following steps:

[0069] (1) The collected waste electronic components of zirconia ceramic parts were crushed to a particle size of less than 5 mm, and then added to a mixture of 10% hydrochloric acid solution and 20% sodium hydroxide solution in a volume ratio of 1:1. After stirring at room temperature for 3-4 hours, the mixture was rinsed with deionized water until neutral and dried to obtain zirconia particles.

[0070] (2) Adding 3% by mass of a Y2O3 stabilizer and 5% by mass of a sodium carboxymethyl cellulose aqueous solution to the above-mentioned zirconium oxide particles, stirring and mixing, and then cold isostatically pressing to obtain a green body, placing the green body in a high-temperature sintering furnace, heating it to 1600°C at a rate of 10°C / min, and keeping it at that temperature for 4 hours to obtain a zirconium oxide ceramic core;

[0071] (3) After the dried rice husk is crushed to a particle size of less than 1 mm, it is placed in a muffle furnace and carbonized at 700 °C for 6 h to obtain carbon powder. The carbon powder, sodium carbonate, and magnesium powder are fully mixed in a mass ratio of 1:3:2, and then placed in a vacuum tube furnace. Under argon protection, the temperature is raised from 7 °C to 850 °C, kept warm for 4 h, and then cooled. The product is placed in a mixture of hydrochloric acid (15%) and HF acid (0.3%) with a volume ratio of 10:1 and soaked for 12 h. The product is washed with water until neutral and then dried to obtain bio-silicon carbide powder;

[0072] (4) Bio-based silicon carbide powder and water were mixed in a mass ratio of 1:5, and then 3% of sodium alginate was added and stirred to obtain a slurry. The slurry was sprayed onto the surface of the zirconia ceramic core by spraying method with a thickness of 25 μm, and then sintered at 1300 °C in an argon atmosphere for 2 h.

[0073] The preparation of the stripping agent comprises the following steps:

[0074] 1) Microcrystalline cellulose was ground and passed through a 100-mesh sieve. The mixture was then mixed with a 60% by mass sulfuric acid solution at a solid-to-liquid ratio of 1:10 and stirred in a 50°C constant temperature water bath for 100 minutes. The sulfuric acid solution was then diluted with deionized water until it was nearly neutral, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until the conductivity of the washing solution was less than 10 μS / cm to obtain cellulose nanocrystals.

[0075] 2) Cellulose nanocrystals were ultrasonically dispersed in an ethanol-water mixture (ethanol:water = 1:1, v / v). After uniform dispersion, 0.1 times the mass of the cellulose nanocrystals was added with APTES. The mixture was stirred at 50°C for 4 h. Unreacted APTES was then removed by dialysis (dialysis bag with a molecular weight cutoff of 3500 Da). The mixture was then acetylated with acetic anhydride to control the degree of substitution to 0.2 to obtain modified cellulose nanocrystals.

[0076] 3) Citric acid and polyethylene glycol 400 were added to a reactor in a molar ratio of 1:3, and then p-toluenesulfonic acid (1% by weight of the citric acid) was added as a catalyst. The esterification reaction was carried out at 130°C for 7 hours. After the reaction, a saturated sodium carbonate solution was added to neutralize the catalyst, and the pH was adjusted to 8. The organic phase was then separated using a separatory funnel, washed with deionized water four times, and then distilled under reduced pressure to obtain a citrate surfactant.

[0077] 4) Glucose and deionized water were mixed in a mass ratio of 1:10, 0.1 M citric acid was added, and a hydrothermal reaction was carried out at 190°C for 4 hours. After the reaction, the mixture was filtered through a 0.22 μm filter membrane and then dialyzed (with a molecular weight cutoff of 1000 Da) to obtain a purified carbon quantum dot solution. Polyethyleneimine accounting for 5% of the mass of the carbon quantum dots was added to the purified carbon quantum dot solution. After stirring at room temperature for 3 hours, the mixture was dialyzed again (with a molecular weight cutoff of 3500 Da) to obtain glucose-derived carbon quantum dots.

[0078] 5) Add modified cellulose nanocrystals, citrate surfactant, and glucose-derived carbon quantum dots to deionized water in a mass ratio of 16:3:1, and stir at 10,000 rpm for 40 minutes at room temperature;

[0079] S3. Centrifuge at 10,000 rpm for 15 minutes to remove the ball milling medium, dialyze (dialysis bag with a molecular weight cutoff of 5,000 Da) for 30 hours to remove the stripping agent, and then freeze-dry.

[0080] Comparative Example 1

[0081] Compared with Example 2, this comparative example 1 is that the nitrogen-water vapor mixed gas in step S1 is replaced by nitrogen, and the other steps are the same as those in Example 2.

[0082] Comparative Example 2

[0083] Compared with Example 2, this comparative example 2 replaces the "first turn on the pulse plasma power supply, adjust the power supply frequency to 10 kHz, the voltage to 100 V, and process for 11 minutes, then adjust the power supply frequency to 50 kHz, the voltage to 300 V, and process for 5 minutes" in step S1 with "turn on the pulse plasma power supply, adjust the power supply frequency to 10 kHz, the voltage to 100 V, and process for 16 minutes", and the other steps are the same as Example 2.

[0084] Comparative Example 3

[0085] Compared with Example 2, the ball milling medium in step S2 was replaced by commercially available ZrO2 spherical grinding balls with a diameter of 10 mm (density 5.8 g / cm 3 ), other steps are the same as those in Example 2.

[0086] Comparative Example 4

[0087] Compared with Example 2, in Comparative Example 4, the stripping agent in step S2 was replaced with a 1% sodium dodecyl sulfate (SDS) aqueous solution, and the other steps were the same as those in Example 2.

[0088] Performance Testing

[0089] 1. Graphene structure and electrical performance testing

[0090] Atomic force microscopy was used to observe the thickness and lateral dimensions of the graphene sheets and calculate the monolayer ratio. Graphene powder was pressed into thin sheets and their room-temperature electrical conductivity was measured using a four-probe instrument. The test results are shown in Table 1 below.

[0091] Table 1

[0092] Single layer rate (%) Conductivity (%) Example 1 76 <![CDATA[1.3×10 5 ]]> Example 2 77 <![CDATA[1.3×10 5 ]]> Example 3 77 <![CDATA[1.3×10 5 ]]> Comparative Example 1 58 <![CDATA[4.8×10 4 ]]> Comparative Example 2 67 <![CDATA[9.5×10 4 ]]> Comparative Example 3 65 <![CDATA[1.0×10 5 ]]> Comparative Example 4 69 <![CDATA[3.9×10 4 ]]>

[0093] As can be seen from Table 1 above, compared with the comparative example, the embodiment significantly improves the monolayer rate and electrical conductivity through dual-mode plasma treatment and optimization of ball milling media and stripping agent.

[0094] 2. Ball milling media performance test

[0095] The media mass was weighed before and after grinding to calculate the wear percentage, and the media performance was evaluated by the amount of graphite removed per unit time. The test results are shown in Table 2 below.

[0096] Wear rate (%) Stripping efficiency (%) Example 2 0.7 1.3 Comparative Example 3 5.2 0.7

[0097] As can be seen from Table 2 above, the ball milling media of the present invention has a wear rate reduced by 86.5% and a stripping efficiency increased by 85.7% compared to commercially available ZrO2 spherical grinding balls with a diameter of 10 mm. The ball milling media of the present invention has better ball milling performance and stability.

[0098] 3. Stripper recycling test

[0099] The stripping agent was recovered and reused, and the change in the graphene monolayer rate after each use was monitored to determine the maximum number of cycles. The test results are shown in Table 3 below.

[0100] Table 3

[0101] Number of cycles Example 2 Single layer rate (%) Comparative Example 4 Single layer rate (%) 1 77 69 5 75 63 10 70 55

[0102] As can be seen from Table 3 above, the monolayer rate of the stripping agent of the present invention remains at 70% after 10 cycles, and the performance is significantly improved compared to Comparative Example 4.

[0103] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing graphene using plasma-assisted ball milling, characterized in that: The steps include: S1, crushing the flake graphite and placing it in a plasma reaction chamber, introducing a nitrogen-water vapor mixed gas, and performing plasma treatment; S2, adding the plasma-treated graphite raw material, ball milling medium, and stripping agent into a ball milling tank for ball milling; S3. Centrifugal treatment is performed to remove the ball milling medium, dialysis treatment is performed to remove the stripping agent, and then freeze-drying treatment is performed.

2. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: The volume ratio of nitrogen to water vapor in the nitrogen-water vapor mixed gas described in step S1 is 8:

2. The plasma treatment is specifically as follows: first turn on the pulse plasma power supply, adjust the power frequency to 10 kHz, the voltage to 100 V, and treat for 10 to 12 minutes, then adjust the power frequency to 50 kHz, the voltage to 300 V, and treat for 5 to 6 minutes.

3. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: The ball-to-material ratio during the ball milling process in step S2 is 15-25:

1.

4. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: The preparation of the ball milling medium described in step S2 comprises the following steps: (1) The collected waste electronic components of zirconia ceramic parts were crushed to a particle size of less than 5 mm, and then added to a mixture of 10% hydrochloric acid solution and 20% sodium hydroxide solution in a volume ratio of 1:

1. After stirring at room temperature for 3-4 hours, the mixture was rinsed with deionized water until neutral and dried to obtain zirconia particles. (2) Adding 3% by mass of a Y2O3 stabilizer and 5% by mass of a sodium carboxymethyl cellulose aqueous solution to the above-mentioned zirconium oxide particles, stirring and mixing, and then cold isostatically pressing to obtain a green body, placing the green body in a high-temperature sintering furnace, heating it to 1600°C at a rate of 8-10°C / min, and keeping it at that temperature for 3-4 hours to obtain a zirconium oxide ceramic core; (3) The slurry is sprayed onto the surface of the zirconia ceramic core using a spraying method, with a thickness of 15-25 μm, and then sintered in an argon atmosphere at 1300 °C for 1-2 hours.

5. The method for preparing graphene by plasma-assisted ball milling according to claim 4, wherein: The preparation of the slurry described in step (3) comprises the following steps: A. After the dried rice husk is crushed to a particle size of less than 1 mm, it is placed in a muffle furnace and carbonized at 700°C for 5-6 hours to obtain carbon powder. The carbon powder, sodium carbonate, and magnesium powder are fully mixed in a mass ratio of 1:3:2, and then placed in a vacuum tube furnace. Under argon protection, the temperature is raised from 6-7°C to 850°C, kept warm for 3-4 hours, and then cooled. The product is placed in a mixture of hydrochloric acid and HF acid with a volume ratio of 10:1 and soaked for 10-12 hours. The product is washed with water until neutral and then dried to obtain bio-silicon carbide powder; B. Mix bio-based silicon carbide powder and water in a mass ratio of 1:5, then add 3% by mass of sodium alginate and stir until well mixed.

6. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: The preparation of the stripping agent described in step S2 includes the following steps: 1) Microcrystalline cellulose was ground and passed through a 100-mesh sieve. The mixture was then mixed with a 60% by mass sulfuric acid solution at a solid-to-liquid ratio of 1:10 and stirred in a constant temperature water bath at 40-50°C for 80-100 minutes. The sulfuric acid solution was then diluted with deionized water until it was nearly neutral, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until the conductivity of the washing solution was less than 10 μS / cm to obtain cellulose nanocrystals. 2) Ultrasonic dispersion of cellulose nanocrystals in ethanol-water solution. After uniform dispersion, 0.1 times the mass of APTES was added to the cellulose nanocrystals. The mixture was stirred at 40-50°C for 3-4 hours. Unreacted APTES was then removed by dialysis. The cellulose nanocrystals were then acetylated with acetic anhydride to a degree of substitution of 0.2, yielding modified cellulose nanocrystals. 3) Add the modified cellulose nanocrystals, citrate surfactant, and glucose-derived carbon quantum dots into deionized water at a mass ratio of 16:3:1, and stir at 8000-10000 rpm for 30-40 minutes at room temperature.

7. The method for preparing graphene by plasma-assisted ball milling according to claim 6, wherein: The preparation method of the citrate surfactant described in step 3) is as follows: citric acid and polyethylene glycol 400 are added to a reactor in a molar ratio of 1:3, and then 1% by weight of citric acid and p-toluenesulfonic acid are added as a catalyst. The esterification reaction is carried out at 120-130° C. for 6-7 hours. After the reaction is completed, a saturated sodium carbonate solution is added to neutralize the catalyst, and the pH is adjusted to 7-8. The organic phase is then separated using a separatory funnel, washed with deionized water 3-4 times, and then distilled under reduced pressure.

8. The method for preparing graphene by plasma-assisted ball milling according to claim 6, wherein: The preparation method of the glucose-derived carbon quantum dots described in step 3) is as follows: glucose and deionized water are mixed in a mass ratio of 1:10, 0.1M citric acid is added, and a hydrothermal reaction is carried out at 180~190°C for 3~4h. After the reaction is completed, it is filtered through a 0.22μm filter membrane, and then dialyzed to obtain a purified carbon quantum dot solution. Polyethyleneimine accounting for 5% of the mass of the carbon quantum dots is added to the purified carbon quantum dot solution, and the reaction is stirred at room temperature for 2~3h, and then dialyzed again to obtain glucose-derived carbon quantum dots.

9. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: During the ball milling treatment in step S2, the ball milling speed is controlled to be 400-600 rpm and the ball milling time is 3-5 h.

10. The method for preparing graphene by plasma-assisted ball milling according to claim 1, wherein: The centrifugal treatment in step S3 is carried out at a rotation speed of 8000-10000 rpm and a centrifugal time of 10-15 min. The dialysis treatment is carried out at a molecular weight cut-off of 3500-5000 Da and a dialysis time of 20-30 h.

Citation Information

Patent Citations

  • Physical striping method of graphene

    CN105712333A

  • Efficient preparation method of graphene

    CN105883763A

  • Method for preparing graphene nano-sheet based on crystalline flake graphite

    CN107720740A

  • Method of producing graphene by stripping graphite via time-space-synchronous ultrasonic treatment and ball-milling process

    CN107879332A

  • Plasma exfoliated graphite material and preparation method thereof

    CN112408383A